Pengaruh Brand Image, Promosi dan Kualitas Produk Terhadap Keputusan Pembelian Smartphone Infinix - Citra Rizkiana; Edy Suryawardana; Putri Pratiwi; Aprih Santoso (ARBITRASE: Journal of Economics and Accounting, 2023)
This study aims to determine: (1) the effect of brand image on Infinix smartphone decisions, (2) the effect of promotion on Infinix smartphone purchasing decisions, (3) the effect of product quality on Infinix smartphone purchasing decisions. The population of this study are consumers who use or buy Infinix smartphones at Pandawa Elektronik Semarang. The sampling technique used probability sampling simple random sampling method, in order to obtain a total sample of 96 respondents. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique uses the classical assumption test, multiple linear regression analysis, t test and the coefficient of determination (R2). The results showed that brand image had a positive and significant effect on purchasing decisions, promotion had a positive and significant effect, product quality had a positive and significant effect on purchasing decisions. The value of the coefficient of determination is 0.571 or 57.1 percent. Purchase decisions are influenced by brand image, promotion and product quality variables, while the remaining 42.9 percent are influenced by other variables outside the model that are not present in this study.